Security Strength Measurement for Dongle-Protected Software. - Piazzalunga, U. (IEEE Security and privacy : building confidence in a networked world)
This article's objective is to develop a model for measuring the security strength of dongle-protected software. We believe such a measure is important because it can attach a clear, simple, and understandable monetization number to security. Dongles are USB keys or small boxes attached to the host parallel port. The copy-protected application interacts with the dongle and progresses its execution only if the dongle answers appropriately. The interaction between the software and the dongle takes place through calls to the dongle API.